Highly sensitive fluorescent single-chain polymeric nanoparticles as chemosensors for selective Fe3+detection - Ozturk, Deniz Kilic; Balta, Demet Karaca; Temel, Binnur Aydogan; Temel, Gokhan (ELSEVIER SCIENCE SA, 2025)
This work describes a straightforward technique for preparing single-chain polymeric nanoparticles by photodimerization of pendant anthracene moieties on the side chain of styrenic and acrylic based linear polymers. The resulting single-chain polymeric nanoparticles (SCNPs) are then converted into pyrene functional nanoparticles through the simple Diels-Alder post-functionalization method. Polymeric nanoparticles containing maleimide and pyrene entities were deployed as a chemosensor capable of selectively detecting Fe3+ ions. Adding Fe3+ ions into achieved nanoparticle medium, color change is readily visible with unaided eye. The chemosensor's ability to sense Fe3+ ions remained unaltered by the presence of other metal ions, such as Al3+, Ba2+, Ca2+, Cr3+, K+, Mg2+, Na+, NH4+, Ni2+, and Sn2+. These results suggest that functional SCNP is a potential probe of Fe3+ ions and it will be beneficial for future SCNP sensor design. They exhibit high sensitivity and selectivity for the detection of Fe3+ in the micromolar concentration range, making it a promising tool for Fe3+ detection even in the presence of other common interfering metal ions.
Keywords: Single-chain polymeric nanoparticle (SCNP); Chain folding; Nanoparticles; Chemosensor; CLICK CHEMISTRY; IRON-DEFICIENCY; FE3+; COVALENT; IONS; Chemistry